Prevalence of tuberculosis, brucellosis and trypanosomiasis in cattle in Tanzania: a systematic review and meta-analysis - Alonso, Silvia; Dohoo, I.; Lindahl, Johanna F.; Verdugo, Cristobal; Akuku, I.; Grace, Delia (Cambridge University Press, 2016)
A meta-analysis was performed to derive prevalence estimates for Brucella spp., Mycobacterium spp. and Trypanosoma spp. in cattle in Tanzania using data derived from a systematic review of zoonotic hazards in cattle production systems. Articles published before 2012 reporting prevalence and considered at least moderate in quality were included in the analysis. Results showed high heterogeneity between studies, with wide ranges in the reported prevalence: Brucella (0.3–60.8%), Mycobacterium (0.1–13.2%) and Trypanosoma (0.82–33.3%). Overall meta-analytic mean prevalence estimates were 8.2% (95% CI 6.5–10.2), 1.28% (95% CI 0.35–4.58) and 10.3% (95% CI 6.20–16.70) respectively, for Brucella spp., Mycobacterium spp. and Trypanosoma spp. Time and region were predictors of variability of Brucella spp. prevalence, while diagnostic test was a strong predictor of Mycobacterium spp. prevalence, with higher prevalence estimates given by skin tests compared with post-mortem inspection. None of the studied factors were associated with prevalence of Trypanosoma spp. The small sample sizes, range of study locations, study designs and diagnostics used, contributed to high variability among prevalence estimates. Larger and more robust prevalence studies are needed to adequately support risk assessment and management of animal and public health threats.